Description of the previously unknown morphs of Periphyllus koelreuteriae (Takahashi) (Hemiptera, Aphididae: Chaitophorinae) - Junkiert, Łukasz; Wieczorek, Karina (Zootaxa, 2019)
The previously unknown morphs of the autumn generations of Periphyllus koelreuteriae (Takahashi, 1919) (Hemiptera, Aphididae: Chaitophorinae)—the viviparous apterous female, the oviparous female and the alate male—are described and illustrated in detail based on specimens that were collected in China. Because P. koelreuteriae is a significant pest species that damages the ornamental and medicinal plants of the genus Koelreuteria, notes on its biology, host plants and distribution are presented.